Meeting Report: 9th Annual Diabetes Nepal Conference - Rajbhandari, Satyan (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
9th Annual Diabetes Nepal Conference and Indo-Nepal-UK Diabetes Meeting was held in Kathmandu on 23rd February 2019.